Apixaban in Comparison With Warfarin in Patients With Atrial Fibrillation and Valvular Heart Disease. Issue 8 (25th August 2015) - Avezum, Alvaro; Lopes, Renato D.; Schulte, Phillip J.; Lanas, Fernando; Gersh, Bernard J.; Hanna, Michael; Pais, Prem; Erol, Cetin; Diaz, Rafael; Bahit, M. Cecilia; Bartunek, Jozef; De Caterina, Raffaele; et al.
<x xml:space="preserve">Abstract</x> Background— Apixaban is approved for the prevention of stroke and systemic embolism in patients with nonvalvular atrial fibrillation. However, the Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation (ARISTOTLE) trial included a substantial number of patients with valvular heart disease and only excluded patients with clinically significant mitral stenosis or mechanical prosthetic heart valves. Methods and Results— We compared the effect of apixaban and warfarin on rates of stroke or systemic embolism, major bleeding, and death in patients with and without moderate or severe valvular heart disease using Cox proportional hazards modeling. Of the 18 201 patients enrolled in ARISTOTLE, 4808 (26.4%) had a history of moderate or severe valvular heart disease or previous valve surgery. Patients with valvular heart disease had higher rates of stroke or systemic embolism and bleeding than patients without valvular heart disease. There was no evidence of a differential effect of apixaban over warfarin in patients with and without valvular heart disease in reducing stroke and systemic embolism (hazard ratio [HR], 0.70; 95% confidence interval [CI], 0.51–0.97 and HR, 0.84; 95%, CI 0.67–1.04; interaction P=0.38), causing less major bleeding (HR, 0.79; 95% CI, 0.61–1.04 and HR, 0.65; 95% CI, 0.55–0.77; interaction P=0.23), and reducing mortality (HR, 1.01; 95% CI, 0.84–1.22 and HR, 0.84; 95% CI, 0.73–0.96; interaction P=0.10). Conclusions— More than a quarter of the patients in ARISTOTLE with nonvalvular atrial fibrillation had moderate or severe valvular heart disease. There was no evidence of a differential effect of apixaban over warfarin in reducing stroke or systemic embolism, causing less bleeding, and reducing death in patients with and without valvular heart disease. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00412984.